AIRCRAFT CABIN AIR QUALITY (Tufts Archival Research Center, 2007)
Confidential; Report on Aircraft Cabin Air Quality analyzing the 1986 proposed smoking ban on all domestic flights. Claims that a smoking ban on all domestic flights is a safety risk and an administrative hassle. Argues that Congress should not pass the ban and focus attention on improving ventilation systems.